Social Network Analysis in the Coastal Area Improvement Initiation Program - Ayu Novelisa (Universitas Andalas, 2019)
The research location is in Bungin Village, Pantai Bakti Village, where the issue is related to the conditions of coastal areas and brings up the program initiation. The research method was carried out with qualitative methods through in-depth interviews and participant observant. This thesis shows that in responding to the initiating improvements program in coastal areas, coastal communities are often faced with the social dynamics of the community itself. The response gap of the actors is influenced by social relations namely, 1) relations based on patron-client, 2) relations based on blood relations, and 3) relations based on emotional relationships, and two economic motives, namely 1) economic motives based on personal gain, and 2) economic motives which are based on basic needs. This thesis also enriches the study of the response of the fishing community through the approach of actor and network analysis. This approach is more relevant in looking at the response to the initiation of improving coastal areas through forms of actions, relationships, roles and motives of actors who are part of coastal communities.